Ingestion and effects of micro- and nanoplastics in blue mussel (Mytilus edulis) larvae. (March 2019) - Rist, Sinja; Baun, Anders; Almeda, Rodrigo; Hartmann, Nanna B.
Abstract: It is well known that mussels are exposed to microplastics but ingestion and potential effects on mussel larvae are not well understood. We quantified ingestion and egestion of 100 nm and 2 μm polystyrene beads in blue mussel larvae after 4 h exposure and 16 h depuration using different plastic-to-microalgae ratios. Effects on growth and development of mussel larvae were investigated at 0.42, 28.2 and 282 μgL −1 within 15 days of exposure. We found that, on a mass basis, larvae ingested a higher amount of 2 μm than 100 nm beads, while egestion was independent of particle size and the plastics-to-algae ratio. Although particle egestion occurred readily, microplastics remained inside the larvae. Larval growth was not affected but abnormally developed larvae increased after exposure to polystyrene beads. Malformations were more pronounced for 100 nm beads, at higher concentration and after longer exposure time. Graphical abstract: Unlabelled Image Highlights: Blue mussel larvae ingested more 2 μm than 100 nm polystyrene beads on a mass basis. Egestion was independent of particle size and the ratio of plastic to food algae. None of the particle sizes were completely egested after up to 48 h in clean water. Abnormal larval development increased during 15 d exposure to both particle sizes. More malformations were observed for 100 nm beads and with longer exposure time.